Estimation of Technical Reserves in Automobile Insurance Using Deterministic and Stochastic Methods - Kamilia BELLAL; Billel BENILLES (Journal of Excellence for Economics and Management Research, 2024)
Insurance companies bear the responsibility of maintaining their financial stability on an ongoing basis. One of the most significant challenges they face in this regard is the inaccuracy of technical reserve estimates for outstanding claims. For this reason, numerous research studies have focused on developing methods to improve the accuracy of these estimates. In this paper, we will present and apply several methods for calculating technical reserve provisions, whether deterministic or stochastic, such as the chain ladder method, the Mack method, the bootstrap method, and generalized linear models (GLMs). These statistical and analytical methods will be applied to a dataset of bodily injury claims in the civil liability arising from automobile accidents, covering the period from 2012 to 2022, and issued by one of the leading insurance companies in the Algerian market. Each method will be described and implemented to provide more accurate reserve estimates. Finally, we will compare the results obtained from each of these methods.